Role of Plant Density on Vegetative Growth and Yield of Four Faba Bean Cultivars - Al-Jubouri, Amer Abdullah Hussein (Journal La Lifesci, 2024)
The study was conducted in the vegetable field of the Department of Horticulture and Landscape Engineering, College of Agriculture and Forestry, University of Mosul, during the agricultural season 2018-2019 to study the effect of plant density on the vegetative growth characteristics and yield of four bean varieties, that is, by two factors: plant density (8 plants / m2 and 12 plants / m2) and cultivars. (Local, Spanish, French, Dutch) within the (RCBD) design with three replications, as the number of transactions in the experiment was (8) . The plant density of 8 plants/m2 showed its superiority in most of the characteristics of vegetative growth and yield, except for the two characteristics of plant height and pod weight, where it was superior under the plant density of 12 plants/m2. The local cultivar excelled in most of the characteristics of vegetative growth and the characteristics of total yield and plant yield compared with the Dutch or French variety. Give the lowest values for these traits.